Is it still worth pursuing the repurposing of metformin as a cancer therapeutic? - Lord, Simon R; Harris, Adrian L (British journal of cancer, 2023)
Over the past 15 years, there has been great interest in the potential to repurpose the diabetes drug, metformin, as a cancer treatment. However, despite considerable efforts being made to investigate its efficacy in a number of large randomised clinical trials in different tumour types, results have been disappointing to date. This perspective article summarises how interest initially developed in the oncological potential of metformin and the diverse clinical programme of work to date including our contribution to establishing the intra-tumoral pharmacodynamic effects of metformin in the clinic. We also discuss the lessons that can be learnt from this experience and whether a further clinical investigation of metformin in cancer is warranted.